2018
DOI: 10.1002/ajim.22815
|View full text |Cite
|
Sign up to set email alerts
|

Occupational asthma risk from exposures to toluene diisocyanate: A review and risk assessment

Abstract: This study synthesized epidemiologic data to characterize the TDI-OA dose-risk relationship. This approach yielded prospective OEL estimates below recent recommendations by the American Conference of Governmental Industrial Hygienists, but given significant study limitations, this should be interpreted with caution. Confirmatory research is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…However, larger isocyanates such as toluene diisocyanate and 4,4 0 -methylene diphenyl diisocyanate have known serious health effects such as asthma, methemoglobinemia and respiratory cancers and are thus regulated for occupational and health in the workplace. [61][62][63] HNCO is the smallest molecule within the class of isocyanates and it is unclear if it triggers similar health effects as its phenyl counterparts. Nonetheless, HNCO has been quantied in the workplace particularly in the welding, paint, and transport industry, where mixing ratios up to 4.4 ppbv have been measured (Table 2).…”
Section: Ambient Measurementsmentioning
confidence: 99%
“…However, larger isocyanates such as toluene diisocyanate and 4,4 0 -methylene diphenyl diisocyanate have known serious health effects such as asthma, methemoglobinemia and respiratory cancers and are thus regulated for occupational and health in the workplace. [61][62][63] HNCO is the smallest molecule within the class of isocyanates and it is unclear if it triggers similar health effects as its phenyl counterparts. Nonetheless, HNCO has been quantied in the workplace particularly in the welding, paint, and transport industry, where mixing ratios up to 4.4 ppbv have been measured (Table 2).…”
Section: Ambient Measurementsmentioning
confidence: 99%
“…Collins et al (2017) reported an average asthma incidence rate of 0.9 per hundred person-years against average TWA values between 0.1 and 3.4 ppb. Daniels (2018) provides an extensive overview but did not include the results of Collins et al (2017) (Supplemental Information-6). None of the exposure-response models evaluated by Daniels (2018) exhibited a significant slope parameter.…”
Section: Discussionmentioning
confidence: 99%
“…NIOSH applied two UFs: a factor of 10 for interspecies variability and another factor of 10 for intraspecies variability (i.e., a divisor of 100). Examples of NIOSH applications of UFs are in risk assessments for carbon nanotubes and nanofibers [NIOSH 2013b] and toluene diisocyanate [Daniels 2018].…”
Section: Application Of Uncertainty Factors (Ufs)mentioning
confidence: 99%
“…In 1995, the Risk Assessment Activity was formally organized. Since that time, NIOSH staff have conducted quantitative risk assessments for a wide variety of agents, including diesel exhaust NIOSH CIB 69 • NIOSH Practices in Occupational Risk Assessment [Stayner et al 1998], 1,3-butadiene [Stayner et al 2000], asbestos [Stayner et al 1997], silica [Park et al 2002;Rice et al 2001], noise (with and without co-exposure to carbon monoxide) [NIOSH 1998], titanium dioxide [NIOSH 2011], hexavalent chromium [NIOSH 2013a], carbon nanotubes and nanofibers [NIOSH 2013b], diacetyl and 2,3-pentanedione [NIOSH 2016], manganese in welding fume [Park and Berg 2018;Park et al 2009], toluene diisocyanate [Daniels 2018], and metalworking fluids [Park 2018] (Table 1-1).…”
Section: Introductionmentioning
confidence: 99%